The Crisis of Meaning in the Age of Meaning: A Literature Review of Semantic Disorders in Social Media - Aswad, Hajar (Wardah, 2025)
The digital era has fundamentally changed the pattern of human communication. One of the significant impacts of this change is the occurrence of a crisis of meaning in online interactions, triggered by the semantic bending in the use of language on social media. Phenomena such as memes, irony, and remix culture also accelerate the process of shift and ambiguity of meaning. This article aims to examine the literature on meaning disorders that occur in the digital space, especially on social media. With the literature study method, the author examines theories of meaning, digital language, and the phenomenon of memes as a form of bending meaning. The results of the study show that social media contributes to semantic crises through the production of meanings that are contextual, fragmented, and often ironic. This article also highlights the urgency of semantic literacy and digital communication ethics as a response to the crisis of meaning in the post-truth era.